Methodological Preconditions of Institutionalization in Educational System of Russia - Nikitovich, Gaponyuk Peter; Alexandrovich, Dyuzhikov Sergey; Konstantinovna, Karpova Natalia; Ivanovich, Mareev Vladimir; Pavlovich, Uvarovsky Alexander (Advances in Social Sciences Research Journal, 2015)
The article covers basic concepts which describe methodological premises of institutionalization of modern education, namely: “innovative quality”, “technologies of training/education” and “ideology of culture”. The authors dwell on the development of institutionalization meta-theory. As for the key principle of the meta-theory, the authors mention its poly-structural nature. The article also provides proofs to support relevance of the use of institutional analysis procedure. The article also describes the algorithm of institutional analysis for functioning and transformation/modernization of institutes that constitute modern educational system of Russia.